Myopic tilted disc: Mechanism, clinical significance, and public health implication - Chan, Poemen P.; Zhang, Yuqiao; Pang, Chi Pui (Frontiers in Medicine, 2023)
Myopic tilted disc is a common structural change of myopic eyes. With advancing ocular imaging technology, the associated structural changes of the eye, particularly the optic nerve head, have been extensively studied. These structural changes may increase patients’ susceptibility to axonal damage and the risk of developing serious optic neuropathies including glaucoma. They also lead to diagnostic difficulties of disease suspects and treatment dilemmas of patients, which implicate clinical practice and subsequently the health care system. In the context of the mounting prevalence of myopia worldwide and its implications to irreversible visual impairment and blindness, it is essential to gain a thorough understanding of the structural changes of myopia. Myopic tilted disc has been extensively investigated by different study groups. However, generalizing the knowledge could be difficult because of the variable definitions of myopic tilted disc utilized in these studies and the complexities of the changes. The current review aimed to clarify the concepts and discuss various aspects of myopic tilted disc, including the definitions, association with other myopia-related changes, mechanism of tilted disc development, structural and functional changes, and clinical implications.